Strategi Pemasaran Snack Mix melalui Platform TikTok terhadap Keputusan Membeli pada Gen Z - Khoirun Nisa; Erlin Maulidatus. S; Sabrienda Najwa. A; Addina Tafaquh. F; Elsa Amelia. A; Novia Dwi Rahmawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
In the ever-evolving digital era, social media has become one of the main pillars in the marketing strategy of various products, including snacks such as snack mix. TikTok, as a rising platform, offers various advantages such as ease of access, creative features, and high viral potential, making it an effective marketing tool, especially among millennials and Gen Z. This research uses a descriptive qualitative method with a literature study approach to examine the effectiveness of TikTok in increasing brand awareness and sales of snack mix products through a case study of the @chikindo_ TikTok account. The results showed that strategies such as creating interesting content, using hashtags, collaborating with influencers, and sales promotions can increase product visibility. However, the effectiveness of these strategies varies, depending on creativity and consistency in implementation. Thus, TikTok is a highly relevant and potential platform to be used in the digital marketing of snack food MSMEs in Indonesia.